Patterns of Care and Outcomes of Elderly Esophageal Cancer Patients Not Meeting Age-based Criteria of the CROSS Trial. (January 2019) - Verma, Vivek; Haque, Waqar; Zheng, Dandan; Osayande, Ferdinand; Lin, Chi
Abstract : Objectives: The CROSS trial established neoadjuvant chemoradiation followed by surgery (nCRT-S) as superior to surgery alone (S) for locally advanced esophageal cancer (EC). However, because patients above 75 years of age were excluded, this comparison cannot be extrapolated to older patients. This study of a large, contemporary national database evaluated practice patterns in elderly patients ineligible for CROSS, and analyzed overall survival (OS) between nCRT+S, S, and definitive CRT (dCRT). Materials and Methods: The National Cancer Data Base was queried for EC patients with cT1N1M0/T2-3N0-1M0 EC (per the CROSS trial) but 76 years and above of age. Multivariable logistic regression ascertained factors associated with nCRT+S (vs. S). Kaplan-Meier analysis evaluated OS; Cox multivariate analysis determined variables associated with OS. Propensity matching aimed to address group imbalances and indication biases. Results: Of 4099 total patients, 594 (14%) underwent nCRT+S, 494 (12%) underwent S, and 3011 (73%) underwent dCRT. Since 2010, trimodality management has risen, corresponding to declines in S and dCRT. Median OS in the respective groups were 26.7, 20.3, and 17.8 months ( P <0.05). Following propensity matching, there was a trend towards higher OS with nCRT-S over S ( P =0.077); dCRT showed poorer OS than nCRT-S ( P <0.001) but was equivalent to S ( P =0.669). Before and following matching, nCRT-S experienced equivalent 30- and 90-day mortality as S ( P >0.05), with lower 30-day readmission and postoperative hospital stay ( P <0.05). Conclusions: Although most older patients not meeting CROSS criteria undergo dCRT, utilization of trimodality therapy is rising. Despite the trend towards higher OS with trimodality therapy without poorer postoperative outcomes, careful patient selection continues to be essential in this population. Abstract : Supplemental Digital Content is available in the text.